Kajian Literatur tentang Pengaruh Logo Halal Terhadap Keputusan Pembelian Konsumen Muslim di UMKM - Fadhil Musyafa; Novien Rialdy (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the influence of halal logos on consumer purchase decisions in MSMEs through a literature review approach. The halal logo is one of the important elements in building Muslim consumer trust and increasing the competitiveness of MSMEs in the local and global markets. This study collects and synthesizes various previous studies that discuss the relationship between halal logos, consumer perceptions, and purchasing decisions. Data collection is carried out through systematic searches in databases such as Google Scholar, with the keywords